Rapid diagnosis of pseudorabies virus infection in swine tissues using the polymerase chain reaction (PCR) - Echeverría, María Gabriela (2000)
In Argentina pseudorabies is an endemic disease. Routine diagnosis is made by virus isolation. It is a very long procedure to carry out and gives variable results depending on the quality of sample, hence the need for effective techniques, which are rapid and not dependent on the isolation of infectious virus. The polymerase chain reaction (PCR) technique has provided a sensitive, specific and rapid mean to detect DNA sequences. This study describes a PCR method for detection of pseudorabies virus sequences in swine tissues. In order to determine the presence of suid herpesvirus-1 DNA and antigens, 36 tissue samples collected from 19 dead pigs, with signs of pseudorabies infection, were examined by PCR, virus isolation and indirect immunofluorescence, respectively. Fifteen out of 19 pigs were positive at least for one tissue by PCR (15/19) while only three pseudorabies virus strains were isolated (3/19). All the amplified products were identified by digestion with Sa/l and hybridization. The method described herein circumvents tedious viral isolation and DNA purification and would be a valuable tool for rapid diagnosis, since it would take less than 5 h to reach an accurate result even in poorly preserved tissue samples.